Use of Artificial Intelligence in the recruitment and selection process: Perceptions of professionals in a non-profit organization (Research, Society and Development, 2025)
The study investigated the perceptions of Recruitment and Selection (R&S) professionals from a nonprofit organization regarding the use of artificial intelligence (AI) in hiring processes. The objective was to understand professionals' level of familiarity with these technologies, identify perceived benefits and limitations, analyze governance and ethical practices, and assess expectations regarding the future role of AI in R&S. A quantitative approach was adopted, applying an online questionnaire to 25 professionals involved in the selection process, with descriptive analysis used to interpret the collected data. Results indicate that most professionals already use AI tools, especially to automate tasks and accelerate processes such as writing job descriptions and emails, initial resume screening, and communication with candidates. A positive perception was observed regarding efficiency, practicality, and improvement in candidate experience. However, significant gaps were identified, including limited technical training, lack of knowledge regarding ethical and legal aspects, and absence of institutional policies for responsible AI use. Reported drawbacks included technical errors and concerns about reduced human interaction in the selection process. It is concluded that AI is consolidated as a strategic support tool in R&S, although it does not replace human judgment. The study highlights the need for continuous training, digital governance, and balance between technology and human interaction to ensure more efficient, ethical, and inclusive hiring processes.